Day-To-Day Monetary Policy and the Volatility of the Federal Funds Interest Rate - Prati, Alessandro; Bartolini, Leonardo; Bertola, Giuseppe (Washington, D.C. : International Monetary Fund, 2000)
We propose a model of the interbank money market with an explicit role for central bank intervention and periodic reserve requirements, and study the interaction of profit-maximizing banks with a central bank targeting interest rates at high frequency. The model yields predictions on biweekly patterns of the federal funds rate's volatility and on its response to changes in target rates and in intervention procedures, such as those implemented by the Federal Reserve in 1994. Theoretical results are consistent with empirical patterns of interest rate volatility in the U.S. market for federal funds.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: United States